2020
DOI: 10.5817/fai2020-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exchange Rate on the Economic Growth in the Turkish Economy

Abstract: The traditional view asserts that there is a positive relationship between the foreign exchange rate and economic growth. So much so that an increase in foreign exchange rates enhances the net export volume and thus positively affects economic growth due to the increasing total demand. However, structural economists argue that there is an inverse relationship between the exchange rate and economic growth. Especially in developing countries, the input structure of production depends on imported capital and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 27 publications
(19 reference statements)
5
26
1
3
Order By: Relevance
“…The author explained this relationship through two main reasons; the first is that depreciated currencies enhances the competitiveness globally and thus increases exports, the second is that depreciated currencies shifts the demand towards domestic goods. This is supported by (Karahan, 2020) as well.…”
Section: Vector Error Correction Model (Vecm)supporting
confidence: 63%
“…The author explained this relationship through two main reasons; the first is that depreciated currencies enhances the competitiveness globally and thus increases exports, the second is that depreciated currencies shifts the demand towards domestic goods. This is supported by (Karahan, 2020) as well.…”
Section: Vector Error Correction Model (Vecm)supporting
confidence: 63%
“…In the long run, the results of the nonlinear ARDL model (see (2020), and Karahan (2020). The finding also indicates that the direct impact of trade openness is negative on GDP but not significant, which is not consistent with previous studies (Lucas Jr, 1988;Redding, 1999;Young, 1991).…”
Section: Results Of the Nonlinear Modelmentioning
confidence: 63%
“…Their results showed that exchange rate volatility only had a short-term effect that would not encourage long-term market competitiveness and would thus eradicate systemic trade deficits. Karahan (2020) found that the impact of exchange rates on Turkey's economic growth was negative during the 2002-2019 period. The same results were found by Fatbardha, Hysa, Ugur, Mirela, and Marian (2020) in 14 Central and Eastern European countries between 2002 and 2018.…”
Section: Relationship Between Economic Growth and Exchange Ratementioning
confidence: 99%
“…The authors clarified this relationship through two main reasons; the first is that depreciated currencies enhance the competitiveness globally and thus increases exports, the second is that depreciated currencies shift the demand towards domestic goods. This could be supported by (Karahan, 2020) as well.…”
Section: Vector Error Correction Modelmentioning
confidence: 55%